Association between Tea-drinking Habits and Anemia on Pregnant Women in Makassar, Indonesia - Sundari Sundari; Nurul Husnah; Suci Avnalurini Sharief; M. Akbar Alwi (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
Background: The condition of anemia in pregnant women in Indonesia is exacerbated by the habits of consuming tea. Anemia in pregnant women is still a health problem and a high-level cause of death that causes maternal bleeding indirectly. In Indonesia, tea is the most consumed beverage after water. The aroma of fragrant tea and its distinctive taste make this drink widely consumed. Tea can also be used as an antioxidant, improve skin, and slim the body. However, tea-drinking habits in pregnant women can affect the risk of anemia because tea contains tannins that can inhibit the absorption of iron. Purpose: To analyze the association between tea-drinking habits and anemia on pregnant women in Makassar, Indonesia. Methods: This was a quantitative study with cross-sectional design. The subject in this study was 36 pregnant women in the 2nd trimester of pregnancy that was chosen by accidental sampling. The analysis that used was chi-square test to examine the association between tea-drinking habits and anemia. A systematic questionnaire was used to collect data by interviewing respondents. Result: Of the 36 pregnant women who always drink tea, 22 respondents (48%) had anemia and 14 respondents (30%) were not anemic. Meanwhile, of 10 respondents who did not have tea consumption habits, 6 respondents (13%) had anemia and 4 respondents (9%) did not suffer from anemia. Chi-square test showed p=1,000 (p>0,05), which means that there was no association between tea consumption and anemia. Conclusion: Tea-drinking habit was not related to anemia in pregnant women in Makassar, Indonesia. Pregnant women may consume tea after eating but they need to control the interval, at least one hour after having a meal to avoid anemia.